Analisa Tingkat Keberhasilan Program Taman Gizi Dikampung Yoboi Kabupaten Jayapura Berdasarkan Indikator Ketahanan Pangan Sustainable Development Goals (SDGs) - Adela Christa Enock; Elisabeth V. Wambrauw; Agus Eko R. Pepekai; Lazarus Ramandey; Tommi Tommi (Fakultas Teknik Universitas Cenderawasih, 2024)
The Nutrition Garden Program in Yoboi Village, Jayapura Regency, aims to enhance the accessibility and availability of nutritious food within the community, as part of efforts to achieve the second Sustainable Development Goal (SDG): ending hunger and improving food security. This study aims to analyze the success rate of the program based on relevant food security indicators and identify factors influencing community participation in the program. The research methodology includes the collection of primary data through in-depth interviews with local residents and quantitative surveys, as well as secondary data from reports, official documents, and related literature. A comparative analysis with similar programs in other regions was also conducted to obtain a more comprehensive overview. The results of the study indicate that the Nutrition Garden Program has made a positive contribution to improving the accessibility and availability of nutritious food for the residents of Yoboi Village. Participants in the program reported an increase in the consumption of vegetables and fruits produced in their home gardens. Additionally, the program has raised awareness about the importance of balanced nutrition and healthy eating habits among the community. However, several challenges have led to a decline in community participation in the program after the Covid-19 pandemic. Identified factors include a lack of sustained support from local authorities, limited resources, and shifts in community priorities post-pandemic. This study provides recommendations to enhance the program's effectiveness through increased socialization, regular training, adequate resource provision, and closer collaboration with relevant stakeholders. In conclusion, despite the challenges, the Nutrition Garden Program has significant potential in supporting food security achievements in Yoboi Village. By implementing the given recommendations, the program is expected to operate more effectively and sustainably, thereby maximizing community participation.